(3GdJbfjGJ GdLHGFjI eY JeGQjf eMdhdI (B:s IRG, IBS, TAP, IFU , TF , IRG/Salaires, Droits de timbre - (3HhRjOI, MejOs ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2017)
(3jJfGhd GdVQGFH Ydi GdONd h GdGQHGM h GdGLhQ HTcd YGe h GdVQjHI Ydi GdONd GdGLeGdj eY OQGSI eNJda CfhGY GdeOGNjd GdUfajI GdNGVYI dgG cPdc GdVQjHI Ydi GQHGM GdTQcGJ HGYJHGQgG JUjH GdGQHGM GdGTNGU GdeYfhjI YcS GdGhdi GdJj JUjH GdGTNGU GdWHjYjI HGdGVGaI Gdi VQjHI GdOaY GdLRGFj GdJj Je GdZGFgG MSH bGfhf GdeGdjI dSfI (B2006 (3aj GjWGQ JNajV GdYHF Ydi Gdecdajf HGdGVGaI Gdi GdVQjHI GdLRGajI GdhMjOI GdeMOKI HehLH bGfhf GdeGdjI dSfI (B2007 (3HGdGVGaI Gdi GdQSe Ydi GdfTGW Gdegfj h GdQSe GdYbGQj h GdVQjHI Ydi GdYbGQ h Ydi GdGedGc h QSe GdJWgjQ h Mbhb GdJSLjd h GdWGHY(B.s
(3GdeQGLY U(B.199 (3bGFeI GdeUWdMGJ GdLHGFjI GdeSJYedI U (B.195 (3CSFdI hJeGQjf eMdhdI U(B. 179s
Keywords: (3GdVQGFHs